Stress, fear, and anxiety among construction workers: a systematic review - Gómez-Salgado, Carlos; Camacho-Vega, Juan Carlos; Gómez-Salgado, Juan; García-Iglesias, Juan Jesús; Fagundo-Rivera, Javier; Allande-Cussó, Regina; Martín-Pereira, Jorge; Ruiz-Frutos, Carlos (Frontiers in Public Health, 2023)
Objectives The aim of this review was to assess the possible risk factors arising from working conditions, that could have an impact on the stress, fear, and anxiety of construction workers. Methods A systematic review was conducted following the PRISMA format in the Pubmed, Cochrane, Web of Science, Scopus, and PsycInfo electronic databases on 3 February 2023, using the following key words: anxiety, stress, fear, and construction workers. Methodological quality was assessed using the critical appraisal tools of the Joanna Briggs Institute. Results A total of 35 studies were included. The results showed a number of conditioning factors for stress, anxiety, and fear among construction workers such as age, inappropriate safety equipment, safety culture, high workload and long working hours, physical pain, low social support from direct supervisor or co-workers, lack of organisational justice and lack of reward, financial situation, maladaptive coping strategies, and characteristics of the pandemic. Conclusions There are a number of risk factors related to working conditions, organisations, and individuals that can affect the levels of stress, anxiety, and fear among construction workers, such as age, work hardship, safety culture and, especially, the long hours that construction professionals work. This may lead to an increase in the number of occupational accidents and higher associated fatality rates.